NEO-JAHILIYAH BEHAVIOR AND CHALLENGES OF ISLAMIC EDUCATION IN MAWU VILLAGE, AMBALAWI-BIMA DISTRICT - Sunandi Mawu; Idhar; Junaidin (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study analyzes neo -jahiliyah behavior and the challenges of Islamic Education in Mawu Village, Ambalawi District , Bima Regency, as a manifestation of moral and spiritual decline similar to the pre -Islamic era of ignorance, as stated by Sayyid Qutb . The background of the problem includes the degradation of the younger generation due to the lack of religious literacy , which gives rise to phenomena such as drug consumption, alcohol, early marriage, theft, and gambling. The purpose of the study is to uncover neo -jahiliyah behavior, the role of Islamic Education in its transformation, and the challenges faced. The research method is qualitative with a case study approach, using observation techniques, semi-structured interviews with key informants (village heads, traditional leaders, religious leaders, educators, and community), and documentation. Data analysis follows the Miles and Huberman model , with a focus on reduction, presentation, and drawing conclusions. The results of the study indicate that neo -jahiliyah behavior in Mawu Village is influenced by weak internal supervision, family role models, and materialistic economic orientation, despite efforts from various parties such as village patrols, traditional activities (rawi rasa), mosque prosperity , and teaching of faith and morals in schools. Islamic education plays a strategic role through a holistic approach (family, community, formal) to shape noble morals and spiritual awareness, supported by verses of the Qur'an ( QS . Al-Mujadalah: 11) and theories such as ta'dib al-Attas and Ulwan's tarbiyah . However, the main challenges include a lack of consistent guidance, the influence of globalization, a permissive environment, and minimal synergy between elements of society. The study's conclusion emphasizes the need for a comprehensive, sustainable, and collaborative Islamic education strategy to change neo -jahiliyyah behavior, so that the generation of Mawu Village returns to Islamic values that balance reason, heart, and revelation.